Public Debt Reporting in Developing Countries - Rivetti, Diego (World Bank, Washington, DC, 2022)
More than 20 developing countries do not publish any data on their sovereign debt. In those that do disclose data, public debt statistics usually do not comply with international standards in terms of coverage and definitions. Some information can be deduced through indirect disclosure of debt statistics to external agents, such as the World Bank and the International Monetary Fund, and this can help minimize data gaps. This paper has two main objectives. First, it measures the extent of transparency in direct reporting and identifies the factors that promote it. The results show that debt transparency is fostered by standardized recording and reporting systems, high levels of external scrutiny (for example, Eurobond issuance and ratings), and the presence of highly skilled staff at the local debt office. Second, the paper describes the reporting ecosystem in which two type of channels (direct and indirect) coexist and provides novel estimates of the data gaps across the two. Cross-comparison of direct reporting and the World Bank–International Monetary Fund Debt Sustainability Analysis shows that deviations in public debt stocks can represent up to 30 percent of national gross domestic product. Based on these results, the paper puts forward a call for action to (i) improve debt transparency by focusing on those factors that best promote transparency; (ii) shifting the focus of multilateral development banks’ operations and technical assistance from indirect to direct reporting; (iii) introducing minimum but enforceable international standards for direct reporting; and (iv) promoting the use of modern and integrated debt recording and reporting systems.